2022
DOI: 10.1177/17446295221136231
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of mental health of staff working with people with intellectual disabilities during COVID-19––A systematic review

Abstract: Background The COVID-19 pandemic has posed a great risk to the mental health of health workers (HWs). There are likely to be particular concerns for staff working with adults with an intellectual disability, where infection control may be more challenging. Method We conducted a systematic review of original research examining the mental health of HWs working with people with intellectual disability, published between March 2020 and July 2021. Results Five original research studies were included. A high proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…This situation caused a further effect: unexperienced DSPs were left alone with no professional supervision at the group homes where the M/M ID lived. This phenomenon was also reported by authors from different countries [ 15 , 31 , 49 , 53 ].…”
Section: Discussionsupporting
confidence: 84%
“…This situation caused a further effect: unexperienced DSPs were left alone with no professional supervision at the group homes where the M/M ID lived. This phenomenon was also reported by authors from different countries [ 15 , 31 , 49 , 53 ].…”
Section: Discussionsupporting
confidence: 84%
“…One of the participants commented on the impact of the ECHO-AIDD CoP and summed it up as ‘Many hands make light work’, reflecting on the collective teaching and learning created through the ECHO and encapsulating the CoP spirit. Given the impact of COVID-19 on the mental health of service providers and feelings of loneliness, 19,36 participants reflected on how the ECHO-AIDD CoP helped reduce professional isolation. The sessions on wellness and wellness strategies offered service providers a greater understanding of their own self-care, which had an impact beyond the ECHO-AIDD programme.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Service providers working with adults with IDD reported high levels of stress in their workplace during the pandemic. 18,19 Tele-education played an important role in supporting the mental health needs of service providers during the pandemic. 14,20,21 Thakur et al 14 reported on the design and delivery of a provincial virtual education programme, 'ECHO Ontario adult intellectual and developmental disabilities: mental health in the time of COVID-19', using this model to support service providers caring for adults with IDD.…”
mentioning
confidence: 99%